(untitled) (Contemporary Mathematics, 2025)
In this paper, we first study topological structures on Γ-BCK-algebras and obtain some of its properties. Next, we introduce the notion of quotient Γ-BCK-algebra by ideals and investigate some of topological properties on a quotient Γ-BCK-algebra. Finally, we define a quotient Γ-BCK-algebras by dual ideals of a Γ-BCK-algebra and give uniform structures on quotient Γ-BCK-algebras.